Some Wild Species of Basidiomycetous Fungi (Polypores & Mushrooms) Found in the Way to Daunne Devi Temple, Daunne, Parasi District, Nepal - Acharya, Rajendra (Journal of Plant Resources, 2022)
The aim of the present study was documentation of some wild species of Basidiomycetous Fungi (Polypores and Mushrooms). The specimens were collected from Daunne Devi temple and its adjoining area, Daunne, Parasi district in October, 2021. Total of 15 species of Basidiomycetous fungi were collected. The identified species represent five orders belonging to seven families and 13 genera. Polyporales was found to be the dominant order in the study area with 8 species which are Daedaleopsis confragosa, Lenzites betulinus, Microporus sp., Microporus xanthopus, Polyporus spp. (2 species), Pycnoporus cinnabarinus, Steccherinum albo-fibrilosa and Trametes versicolor followed by Agaricales belong to the species of Echinoderma asperum and Schizophyllum commune and Hymenochaetales includes Hymenochaete sp. and Phellinus gilvus. Auriculariales and Corticales are represented by single species each.